Precision Interventional Brachytherapy: A Promising Strategy Toward Treatment of Malignant Tumors - He, Pan; Guan, Siwen; Ren, En; Chen, Hongwei; Chen, Hu; Peng, Yisheng; Luo, Bin; Xiong, Yongfu; Li, Bo; Li, Jingdong; Mao, Jingsong; Liu, Gang (Frontiers in Oncology, 2021)
Precision interventional brachy-therapy is a radiotherapy technique that combines radiation therapy medicine with computer network technology, physics, etc. It can solve the limitations of conventional brachytherapy. Radioactive drugs and their carriers change with each passing day, and major research institutions and enterprises worldwide have conducted extensive research on them. In addition, the capabilities of interventional robotic systems are also rapidly developing to meet clinical needs for the precise delivery of radiopharmaceuticals in interventional radiotherapy. This study reviews the main radiopharmaceuticals, drug carriers, dispensing and fixation technologies, and interventional robotic precision delivery systems used in precision brachytherapy of malignant tumors. We then discuss the current needs in the field and future development prospects in high-precision interventional brachytherapy.